การนำกระบวนการยุติธรรมเชิงฟื้นฟูมาใช้กับคดีข่มขืนกระทำชำเรา - วฐาพร เอื้ออารักษ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
Thailand’s current criminal justice system, "the Retributive Justice," focuses on proving guilt and punishing the offenders. However, rape is a crime of multiple special features with complexities of causes, patterns and impacts of the offense. Rape prosecution and punishment of offenders by the criminal justice system are currently undergoing three problems. Firstly, the victim’s damage, particularly the emotional one, is not properly repaired. Secondly, offenders are not rehabilitated in accordance with the actual causes of the offense. And thirdly, people at large are at risk of rape recidivism as the present criminal justice system does not focus on dealing with the offenders’ intrinsic problems that lead to rape recidivism. The United States of America (State of Arizona), New Zealand and Canada (State of Manitoba) have experienced problems of the criminal justice system in dealing with cases of rape as in Thailand. They all have adopted "the Restorative Justice," a process that focuses on repairing the victim’s damage, rehabilitating offenders and restoring peace and safety in society with the aim of solving problems and improving the administration of justice in rape cases. This thesis is aiming at analyzing the application of restorative justice in rape cases in Thailand. The issues of analyzing are forms of restorative justice applied to rape cases, conditions of applying, steps and restorative process in rape cases, outcome of the application of restorative justice in rape cases as well as the pros and cons, problems and obstacles of applying restorative justice in rape cases. It is anticipated that victims will be more involved in the justice process and be more satisfactorily repaired. Offenders will also obtain appropriate rehabilitation in accordance with the causes of offense and will not be prone to recidivism. And society will be more peaceful and more secure.